STRATEGI PENGEMBANGAN USAHA ANGKRINGAN HERBAL DEWUYUNG DENGAN MENGGUNAKAN ANALISIS SWOT - Erik Bagus Setiawan; Reza Widhar Pahlevi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to know the position of competition and Marketing Strategy with SWOT analysis, strengths, weaknesses, opportunities, and threats. This study was conducted at Angkringan Herbal Dewuyung. The result of descriptive analysis showed that Angkringan Herbal Dewuyung has strength and opportunities than the competitors such as it using social media as the marketing media. It also has different variety of menu than other angkringan. The location of angkringan is near to Nologaten ecotourism village. In addition, there are some weaknesses and threats of Angkringan Herbal Dewuyung. They are the price is little more expensive than other angkringan and the location of Angkringan Dewuyung is located in the alley. The conclusion is the marketing strategy owned by Angkringan Dewuyung has more strengths and opportunities than weakness and threats.